4CPS-207 Treatment adequacy in domiciliary care programme patients. (24th March 2020) - Salom, C; Campabadal, C; Muiño, I; Carrillo, C; Bejarano, F; Marco, N; Del Estal, J; Muniain, MP; Roch, MÁ; Palacios, L; Canadell, L
Abstract : Background and importance: In our area, 77.2% of patients in the domiciliary care programme (ATDOM) are polymedicated and therefore have greater morbidity. Aim and objectives: To analyse a medication plan (MP) review based on criteria of efficacy, efficiency and safety, adapting the treatments of ATDOM patients. Material and methods: This was a retrospective longitudinal study of a prospective cohort including ATDOM patients from a single health centre. Demographic variables (age and sex), type of incidents, proposals, acceptance, application or reasons for non-application, savings and polypharmacy reduction were collected. The pharmacist made proposals based on the clinical review of the MP. If the physician accepted the proposal, the patient/family member was informed for shared decision making. Applications were checked at 3 months. Results: Sample size: 122 of 142 patients were included, 84 (68.8%) women, aged ≥ 65 years. Excluded were 13 (9.1%) patients who died and 7 (4.9%) who were institutionalised. There were 167 incidents involving 161 drugs and 79 (64.7%) patients: 70 (41.9%) related to indications, 49 (29.3%) to effectiveness–efficiency, 35 (21%) to adequacy and 13 (7.8%) to safety. Submitted proposals were 169, suggesting drug suspension in 118 (69.8%), dose change in 18 (10.6%), medication change in 14 (8.3%), therapeutic equivalent change in 12 (7.1%), monitoring in 5 (3%) and frequency change in 2 (1.2%). For 11 (6.8%) drugs it was agreed that the change was not possible. The remaining 93.2% were accepted by the physician. A total of 76 (50.7%) changes were applied, resulting in an annual theoretical saving of 10 546€, and 74 (49.3%) were still pending, involving 49 patients. One patient's family did not accept the proposal, and 5 patients had not been visited. Drugs were reduced from 347 to 279 (19.6%) in 43 (54.4%) patients. Drugs per patient decreased from 8.1±3.2 to 6.5±3.2, which is a reduction of 1.6 drugs/patient. Conclusion and relevance: Physician acceptance of the proposals was high, but almost one half were not carried out despite having been visited. Most pending proposals could be due to organisation or registration mistakes. Suggestions for improvement: (1) to stratify patients according to clinical characteristics that allow prioritisation; (2) to add in situ review of the drug's kit at home, thus allowing a thorough check, including adherence, isoappearance, conservation and administration. References and/or acknowledgements: No conflict of interest.